The Character Development of Students at SMKN 3 Salatiga Through Extracurricular Activities in 2018/2019 Academic Year - Setyani, Intan Putri; Mediatati, Nani (LPPM Undiksha, 2019)
This study aimed to describe the character development of Students at SMKN 3 Salatiga through scout extracurricular activities in] 2018/2019 academic year. The subject of this research were tenth grade students of SMKN 3 Salatiga, amount to 227 students. This research is Qualitative research. The data collected by interviews, observation and questionnaires. The results showed that the characters of students formed and fostered in scout extracurricular activities were religious characters, love of nature, caring for others, patriotism, deliberation, cooperation, skillful, discipline, responsible, honest, love the motherland. Scout activities programs that are designed and implemented to shape and foster student character include training, bantara monitoring, Outbound, Deliberation, camp, flower sowing, and ETK. The success of students' character formation and coaching through the scout program reached an average of 90.08% with a very good category.